Pengaruh Kualitas Pelayanan Islami Terhadap Kepuasan Donatur LAZISMU Kabupaten Mojokerto - Syakuro, Ahmad Abdan; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2020)
The potential of zakat that has not been realized makes each zakat management institution required to plan a good marketing strategy through quality services and in accordance with Islam. LAZISMU is a national scale zakat institution (LAZNAS), but in the middle of its journey LAZISMU stopped temporarily and is not operating, so in this case it is interesting to check whether zakat management institutions that stop on a national scale can still provide good quality services and can satisfy donors. The purpose of this study is to find out how the influence of the quality of Islamic services on donor satisfaction in LAZISMU in Mojokerto district. Quantitative research used in this study with a total sample of 77 LAZISMU donors in Mojoketo Regency. To obtain data using a questionnaire questionnaire with a closed model. Data analysis uses simple linear regression analysis test, partial test (t test) classic assumption test. The results found that the t test was at a significance value of 0,000 <0.05, which means that service quality variables had a significant and positive effect on donor satisfaction. While the test results of the coefficient of determination (R2) are at a value of 36.3%, meaning that the quality of service variable has a contribution of 36.3% to donor satisfaction.